Characterisation of the Phaeosphaeria nodorum and Mycosphaerella graminicola populations of wheat in South Africa - Van der Bank, Judith (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric..) -- University of Stellenbosch, 1998.